Simulasi Permainan Gasing Tradisional Menggunakan Teknologi Virtual Reality Untuk Pelestarian Kebudayaan Tak Benda - Sianturi, Kevin; Akbar, Reza Mochamad; Fauzi, Amir Hasanudin (eProceedings of Applied Science, 2025)
Abstract— The traditional gasing game is an intangible cultural heritage that is increasingly being forgotten with the advancement of technology and changes in modern lifestyles. Preservation efforts are crucial so that this heritage does not become extinct and remains recognized by future generations. Therefore, this study aims to develop a simulation of the traditional gasing game using Virtual Reality (VR) technology as a medium for education and cultural preservation. This application is designed for users to experience playing gasing virtually by presenting realistic game mechanics and supportive traditional environmental visualizations. The development process involves the implementation of an accurate physics simulation for the top's movement, intuitive user interaction design via VR controllers, and an interface integrated with cultural educational content. Through this application, users can learn how to play, the history, and the philosophical values contained within the gasing game. User testing results show that this application not only provides a fun and immersive experience but also significantly increases understanding of and interest in the traditional gasing game. Thus, this research proves that digital media such as VR are effective in raising awareness of the importance of preserving intangible cultural heritage. Keywords— Virtual Reality, cultural preservation, traditional games, gasing, simulation.